2014
DOI: 10.3390/cancers6010240
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinase B/MMP-9 in Tumour Pathogenesis and Progression

Abstract: Since its original identification as a leukocyte gelatinase/type V collagenase and tumour type IV collagenase, gelatinase B/matrix metalloproteinase (MMP)-9 is now recognised as playing a central role in many aspects of tumour progression. In this review, we relate current concepts concerning the many ways in which gelatinase B/MMP-9 influences tumour biology. Following a brief outline of the gelatinase B/MMP-9 gene and protein, we analyse the role(s) of gelatinase B/MMP-9 in different phases of the tumorigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 387 publications
(563 reference statements)
3
149
0
3
Order By: Relevance
“…Matrix metalloproteinase (MMP)-9, one of the proteases present in the extracellular environment, cleaves the ectodomain of membrane-bound E-cadherin at the MMP cleavage site between amino acids Leu581 and Ser582 to generate a 80-kDa fragment referred to as soluble E-cadherin (sE-cad) (De Wever et al, 2007;Maretzky et al, 2005). MMP-9 levels are elevated in several cancers, and this enzyme appears to be involved in tumor cell initiation and progression, metastatic ability and genetic instability (Farina and Mackay, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase (MMP)-9, one of the proteases present in the extracellular environment, cleaves the ectodomain of membrane-bound E-cadherin at the MMP cleavage site between amino acids Leu581 and Ser582 to generate a 80-kDa fragment referred to as soluble E-cadherin (sE-cad) (De Wever et al, 2007;Maretzky et al, 2005). MMP-9 levels are elevated in several cancers, and this enzyme appears to be involved in tumor cell initiation and progression, metastatic ability and genetic instability (Farina and Mackay, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TIMP1 participates in the majority of the physiological and pathological processes involved in cell proliferation, migration, matrix remodeling, cell survival and matrix degradation (14)(15)(16)(17)(18). It has also been reported that TIMP1 is overexpressed in colorectal and lung tumors (19,20), and is associated with metastasis and invasion in breast, upper urinary tract and oral squamous cell tumors (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 influences the development of several human malignancies by, degradation of collagen IV in the basement membrane and the ECM promotes tumor progression, including invasion, metastasis, growth and angiogenesis (Morrison et al, 2001;Stamenkovic, 2000). MMP-9 is produced and secreted by many types of host stromal cells, inflammatory cells and malignant cells (Coussens and Werb, 1996;Farina and Mackay, 2014). In ovarian cancer cell lesions, it was observed that macrophage infiltration was decreased in MMP-9 deficient mice (Huang et al, 2002).…”
Section: Mmp-9 and Tumor Metastasismentioning
confidence: 99%
“…MMP-9 plays a central role in tumor progression, including stromal remodeling, eventually metastasis, rheumatoid arthritis, arteriosclerosis and angiogenesis (Farina and Mackay, 2014;Kupferman et al, 2000). MMPs such as MMP-9 are involved in the development of several human malignancies, as degradation of collagen IV in basement membrane and extracellular matrix facilitates tumor progression, including invasion, metastasis, growth and angiogenesis (Groblewska et al, 2012).…”
Section: Introductionmentioning
confidence: 99%